Dawn-dusk asymmetries of Pc 5 magnetic pulsations - Yumoto, Kiyohumi; Sakurai, Tohru; Saito, Takao (1983)
P(論文) Characteristics of Pc5 magnetic pulsations are analyzed with data of OGO-5 and ISEE-1. Ground characteristics of Pc5 are also reviewed to discuss the correlations with those in space. The occurrence of Pc5 in space increases with an increase in the solar wind velocity, that is consistent with the result of the ground observations. The most common Pc5 pulsations observed at OGO-5 tend to take place while the IMF is in the Parker spiral direction. The toroidal modes (δB_D>>δB_H) of Pc5 pulsations are observed at a higher magnetic latitude and in a localized region of the dawn-side magnetosphere. The compressional and poloidal modes (δB_∥∿δB_H>δB_D) of Pc5 pulsations which penetrate from outside into the inner magnetosphere are mostly observed near the magnetic equator in the dusk-side magnetosphere. This local time asymmetry in the occurrence of dominant modes of Pc 5's in space can be explained by the velocity shear instability in the magnetospheric boundary layer with respect to characteristics of Alfvenic waves in the IMF region and the relation between the IMF direction and the Pc5 occurrence in the magnetosphere. The asymmetrical behavior of Pc5 pulsation activity on the ground across the noon meridian can be explained by the screening effect in the atmosphere and the ionosphere, because of the suppression of the compressional modes with a large horizontal wave number in the dusk-side magnetosphere throughout the atmosphere and the ionosphere. departmental bulletin paper